Starting a business as part of the LAG „Beskid Gorlicki” recruitment in the context of structural changes in the area of industry and services - Ćwikła, Mateusz (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2021)
In the Gorlice poviat (Poland), in recent years, people starting a business activity could take advantage of several different support initiatives that were co-financed from European Union funds. These projects include undertaking business activity under the Rural Development Program for 2014-2020, run by LAG “Beskid Gorlicki”. The aim of the study is to describe the EU funds for undertaking business activities under the Rural Development Program for 2014-2020, run by the LAG “Beskid Gorlicki”. The subject of the study was also the analysis of the existing trends in the context of structural conditions, based on the Polish Classification of Activities (PKD). In 2017-2019, the LAG “Beskid Gorlicki” conducted several recruitments as part of starting a business. In total, out of 97 submitted applications, 62 of them were approved, which constituted 64% of operations within the limit of available funds. A total of PLN 3.72 million was spent under four calls for proposals. The largest number of subsidies was granted to entities included in section F - construction (PLN 720,000, which constitutes a total of 19.4% of the total amount spent in the analyzed period) and section C - industrial processing (PLN 660,000, in total 17.7%). A relatively large percentage of granted subsidies (14.5% each) in the amount of PLN 540,000 each went to sections M - professional, scientific and technical activities and S - other service activities.